Digital Innovation in Enhancing Competitiveness of Destination Marketing Strategy - Ziqrurrahman Irsyad; Muhammad Fuzail; Dedy Iswanto; Mohammad Gamri (Aurora: Journal of Emerging Business Paradigms, 2025)
This research aims to analyze the role of digital innovation in improving the competitiveness of tourist destination marketing strategies with a Systematic Literature Review approach. Literature sources were taken from Google Scholar, Scopus, and DOAJ indexers, with a focus on publications between 2014 and 2024. The results show that the application of digital technology in destination marketing has a significant impact on tourist attraction and satisfaction. Innovations such as social media, virtual reality, and digital content have proven to be effective in increasing destination visibility and enhancing the traveler experience. The characteristics of digital technologies, including their ability to provide real-time and interactive information, play an important role in influencing traveler decisions. However, the research also identified challenges such as the digital divide and potential loss of cultural authenticity that need to be addressed, as they may reduce the effectiveness of marketing strategies. Therefore, the balance between digital innovation and preservation of local culture is a key factor in creating an effective and sustainable marketing campaign. The findings are expected to provide insights for destination managers in designing marketing strategies that are more innovative and responsive to changing tourism trends.